The Development of Coffee Agrotourism Packages as A Product Innovation in Sidomulyo Tourism Village, Jember Regency - Wardani, Peni Arianita; Farhan, Muhamad (Graduate School, Universitas Brawijaya, 2024)
Sidomulyo is a coffee-producing tourism village in Jember Regency. Since its establishment in 2017, Sidomulyo Tourism Village has not received regular tourist visits. This tourism village needs more ready-to-be-offered tourism products for tourists. This study aims to analyze the development of coffee agrotourism packages as a product innovation in Sidomulyo Tourism Village. The qualitative method is used to obtain comprehensive data. Observation, interviews, and documentation were done to collect the data. Data analysis is conducted descriptively based on the tourism package subsystem, including tourists, attractions, facilities, and time. Then, from the analysis, agrotourism packages are formulated following the potential and the market of Sidomulyo Tourism Village. As a result, the agrotourism packages that can be developed in Sidomulyo Tourism Village are Sidomulyo Coffee Experience, Sidomulyo Coffee Edutourism, Sidomulyo Camping Experience, and The Meaningful Life of Sidomulyo.